2016
DOI: 10.1080/00207454.2016.1175441
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of interleukin-33 is associated with poor prognosis of patients with glioma

Abstract: Interleukin-33 (IL-33) has shown diagnostic and prognostic values in multiple human cancers. However, there is little knowledge on the role of IL-33 in human gliomas and its association with disease prognosis. This study aimed to evaluate the value of IL-33 in the prognosis of glioma patients. The expression of IL-33 was determined and compared in surgical specimens from 86 glioma patients and 16 normal brain tissues. The associations of IL-33 expression with the clinicopathological features and prognosis of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Recently, IL-33 was shown to be correlated with a bad prognosis in several types of cancer, although in some cases IL-33 behaves as a tumor suppressor by inducing an immune response. In terms of bad prognosis, high levels of IL-33 were detected in the serum and tumors of patients with glioma ( 56 ), gastric cancer ( 57 ), hepatocellular carcinoma ( 58 ), uterine leiomyoma ( 59 ), lung cancer ( 60 ), colorectal cancer ( 61 ), head and neck squamous cell carcinoma ( 62 ), and breast cancer ( 63 ), when compared to corresponding healthy tissues. The Cancer Genome Atlas Pan-Cancer analysis project showed and declared that the level of IL-33 expression is altered in only 3% of ~580 tumors and that the most common genetic alteration is the deletion of the IL-33 gene ( 64 ).…”
Section: Il-33 As a Marker For Good Or Poor Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, IL-33 was shown to be correlated with a bad prognosis in several types of cancer, although in some cases IL-33 behaves as a tumor suppressor by inducing an immune response. In terms of bad prognosis, high levels of IL-33 were detected in the serum and tumors of patients with glioma ( 56 ), gastric cancer ( 57 ), hepatocellular carcinoma ( 58 ), uterine leiomyoma ( 59 ), lung cancer ( 60 ), colorectal cancer ( 61 ), head and neck squamous cell carcinoma ( 62 ), and breast cancer ( 63 ), when compared to corresponding healthy tissues. The Cancer Genome Atlas Pan-Cancer analysis project showed and declared that the level of IL-33 expression is altered in only 3% of ~580 tumors and that the most common genetic alteration is the deletion of the IL-33 gene ( 64 ).…”
Section: Il-33 As a Marker For Good Or Poor Prognosismentioning
confidence: 99%
“…Lu and collaborators detected “significantly higher IL-33 expression in glioma tissues than in normal brain tissues through immune-histochemical (IHC) analysis” ( 56 ). High IL-33 expression in glioma was correlated with shorter overall survival (OS) and progression-free survival (PFS) ( 56 ).…”
Section: Il-33 As a Marker For Good Or Poor Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was reported that IL-33 is highly expressed in glioma cells and facilitates cell proliferation and migration via the regulation of growth factor and chemokine expression ( 24 ). Previously, we detected the overexpression of IL-33 in glioma tissues compared with that in normal brain tissues, and identified IL-33 overexpression as an independent factor that predicted a poor prognosis in patients with glioma ( 25 ). However, the underlying molecular mechanisms of the IL-33/ST2 axis during glioma development remain to be elucidated.…”
Section: Introductionmentioning
confidence: 97%
“…Pullen et al myeloid granulocytes have gained attention in other areas, especially due to proven alternative, IgE-independent activation schemes, notably through IL33/ST2, and for their potent nociceptive effects on the somatosensory system (though mechanistic details are scant). A timely review of mast cells in neuroinflammation is explained by Skaper et al 180 Astrocytes are known to activate microglia through IL33, 181 and furthermore there are reports linking IL33 induction with decreased survival time 182 and IL33 stimulating expression of MMP2 and MMP9 from immortal cell cultures. 183 Of note is that IL33 positively regulates mast-cell survival and inflammatory functions, [184][185][186] and thus it will be important to investigate a potential pathological link between gliomas and mast cells via IL33 signaling.…”
mentioning
confidence: 99%